Improving Employee Performance Through Workload and Work Motivation at the Darunnajah Islamic Boarding School - Mastur, Mastur; Hafidz, Putra; Fitriani, Eka; Dzulfikar, Dzulfikar; Sativa, Risya Oriza (Journal of Applied Management Research, 2023)
Islamic boarding schools as Islamic educational institutions are needed by the community, but their existence requires good management for the sustainability of the Islamic boarding school itself. This sustainability can be realized by improving the performance of employees in a pesantren, with improved performance it will have an effect on the sustainability of the pesantren itself. This good performance can be obtained by providing workloads that are adjusted to their competence. In addition, good performance can be influenced by high employee motivation. The research sample consisted of 33 employees using smart PLS data analysis. with the results of research 1) workload has no significant effect on employee performance. 2) Workload has a positive and significant effect on work motivation. 3) Work motivation has a positive and significant effect on employee performance. 4) Work motivation is capable of mediating between workload and employee performance.